Obesity and its impact on reproductive medicine - Rechkemmer, Adolfo (2025)
Obesity has a negative impact on reproductive health, with a higher incidence ofanovulation, menstrual disorders and infertility. The increase in adipose tissueis associated with insulin resistance and hyperinsulinemia, reduction in sexhormone binding globulin levels, and hyperandrogenemia. There is an increasein pro-inflammatory adipokines and a decrease in adiponectins. Female obesity isassociated with ovulatory dysfunction, lower ovarian response to ovulation inducers,decreased oocyte quantity and quality, and alteration in endometrial receptivity.Likewise, a decrease in the live birth rate has been reported in in vitro fertilizationtreatments, and an increase in the frequency of abortions. Male obesity increases theincidence of erectile dysfunction and alterations in sperm quality. Diet, exercise, andmedical therapy have been shown to be effective. Bariatric surgery is an alternativein cases of body mass index greater than 40, and achieves a rapid and effectiveweight reduction, with improvement in metabolic parameters; it is recommendedto postpone pregnancy in women for at least one year after surgery. Bariatricsurgery significantly reduces the risk of fetal macrosomia, pregnancy-associatedhypertension, and gestational diabetes. However, it increases the risk of maternalanemia and small-for-gestational-age newborns.